Central pressure – a useful parameter or another scientific fad? - Abramczyk, Piotr; Dobosiewicz, Anna (Przewodnik Lekarza/Guide for GPs, 2008)
Aortic blood pressure reflects peripheral resistance, arterial stiffness and systolic function of the left ventricle. Applanation tonometry is a useful method of assessing central blood pressure and its components (augmentation pressure, augmentation index, time of reflected wave, central pulse pressure). Clinical studies give evidence that aortic blood pressure indices have a significant predictive value in patients with hypertension, left ventricle hypertrophy and ischaemic heart disease. Different influence of cardiovascular drugs on central blood pressure may have practical implications. In the near future, central blood pressure may become a helpful parameter to stratify patients with cardiovascular diseases.